Seismic Behavior Evaluation of Steel Frames Equipped with Rotational Friction Damper (Journal of Civil Engineering Researchers, 2026)
In performance-based seismic design, controlled dissipation of earthquake energy without damage to primary structural members is of great importance. Rotational friction dampers (RFDs) are considered an effective solution due to their stable hysteretic behavior and high energy dissipation capacity. However, direct simulation of the nonlinear behavior of RFDs is difficult in conventional linear analyses. In this study, an equivalent linear model for the RFD based on the principle of work-energy equivalence is presented, in which the equivalent rotational stiffness and equivalent viscous damping parameters are derived from kinematic relationships and Coulomb friction. The proposed model is implemented in ETABS software as a linear Link element with a rotational degree of freedom.To evaluate its performance, a one-story, one-bay steel frame was analyzed under three different configurations: (1) an intermediate moment frame (IMF), (2) an IMF with a chevron brace, and (3) an IMF with a chevron brace and an RFD. A linearized time-history analysis was conducted using the El Centro earthquake record. Numerical results show that the simple moment frame (M1) has a maximum displacement of 0.60 cm (drift 0.20%) and a beam moment of 3.5 kN·m. Adding the chevron brace (M2) reduces the displacement to 0.001 cm (a reduction of 99.8%) and the beam moment to 1.2 kN·m (a reduction of 65.7%), but the brace axial force reaches 15 kN. Adding the RFD (M3), while maintaining high stiffness (period 0.0785 sec), reduces the brace axial force by 20% (to 12 kN) and the beam moment by 16.7% (to 1.0 kN·m) compared to M2. Furthermore, the RFD reduces the velocity amplitude, increases the oscillation damping ratio, and improves dynamic stability.The proposed equivalent linear model provides a simple and reliable method for simulating RFDs in practical engineering analyses and demonstrates that the rotational friction damper can serve as an effective solution for reducing internal member forces and enhancing dynamic stability in braced frames.
Keywords: Rotational Friction Damper (RFD); Equivalent Linear Model; Steel Moment Frame; Chevron Brace; Time-History Analysis